Mitochondrial Toxicity of Selected Micropollutants, Their Mixtures, and Surface Water Samples Measured by the Oxygen Consumption Rate in Cells. (5th April 2019) - Müller, Maximilian E.; Vikstrom, Sofia; König, Maria; Schlichting, Rita; Zarfl, Christiane; Zwiener, Christian; Escher, Beate I.
Abstract: Some environmental pollutants impair mitochondria, which are of vital importance as energy factories in eukaryotic cells. Mitochondrial toxicity was quantified by measuring the change of the oxygen consumption rate (OCR) of HepG2 cells with the Agilent Seahorse XF e 96 Analyzer. Various mechanisms of mitochondrial toxicity, including inhibition of the electron transport chain or adenosine triphosphate (ATP) synthase as well as uncoupling of oxidative phosphorylation, were differentiated by dosing the sample in parallel with reference compounds following the OCR over time. These time–OCR traces were used to derive effect concentrations for 10% inhibition of the electron transport chain or 10% of uncoupling. The low effect level of 10% was necessary because environmental mixtures contain thousands of chemicals; only few of them interfere with mitochondria, but the others cause cytotoxicity. The OCR bioassay was validated with environmental pollutants of known mechanism of mitochondrial toxicity. Binary mixtures of uncouplers or inhibitors acted according to the mixture model of concentration addition. Uncoupling and/or inhibitory effects were detected in extracts of river water samples without apparent cytotoxicity. Uncoupling effects could only be quantified in water samples if inhibitory effects occurred at lower concentrations because no uncoupling can be detected without an appreciable membrane potential built up. The OCR bioassay can thus complement chemical analysis and in vitro bioassays for monitoring micropollutants in water. Environ Toxicol Chem 2019;00:1–12. © 2019 SETAC Abstract : Mitochondrial toxicity in water extracts measured by the oxygen consumption rate (OCR) in cells. Agents that uncouple the oxidative phosphorylation (e.g., bromoxynil) increase the cellular OCR and those that inhibit the electron transport chain (e.g., azoxystrobin) decrease OCR.